Analisis Penggunaan Media Spin The Wheel Wordwall dalam Peningkatan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Hidayah, Eva Nur; Rokhim, An Najmun Nuri; Listia, Dian; Perdana, Oktana Wahyu (Faculty of Teacher Training and Education of Undaris, 2025)
This study aims to analyze the use of Spin The Wheel media on the Wordwall platform in improving the critical thinking skills of fourth-grade students of SDN Gondoriyo, especially in learning Pancasila Education on the material of rules and norms. The background of this study is the low critical thinking skills of elementary school students caused by the dominance of conventional learning methods and the lack of use of interactive learning media. This research used a qualitative approach with a descriptive method. The research subjects consisted of teachers, students, and principals. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis used an interactive model that included data reduction, data presentation, and conclusion drawing. The results showed that Spin The Wheel Wordwall media significantly increased students' participation and critical thinking skills. Students are more active in discussing, expressing opinions, and providing solutions to the cases presented. This media also creates a fun learning atmosphere, encourages collaboration, and contextualizes understanding of social norms. The use of this media faces several challenges, such as limited technological infrastructure, a lack of teacher competence in operating digital media, and limited time for curriculum integration. However, these challenges can be overcome through strategies to improve facilities, gradual teacher training, and flexible management of time and learning methods. Keywords: critical thinking, Pancasila education, interactive media, Wordwall, Spin The Wheel